The Victorian moo-ders : Cows in Action - "Cole, Stephen" , "Fox, Woody" (London; Red Fox, 2010)
Sent back to Victorian England, the C.I.A. is investigating a series of strange moo-ders that seem to have been committed by a ghostly cow of doom who leaves a mysterious black calling card for each of his victims. But what have the F.B.I. got to do with these murders and who will be next? The time-travelling cows need to find out, quickly
Keywords: English fiction-Detective and mystery stories